Top management commitment, corporate social responsibility and green human resource management: A Malaysian study - Yusliza, M.-Y.; Nurul Aimi, Norazmi; Jabbour, Charbel Jose Chiappetta; Fernando, Yudi; Fawehinmi, Olawole; Seles, Bruno Michel Roman Pais (Emerald, 2019)
The purpose of this paper is to analyse the relationship between top management commitment, corporate social responsibility (CSR) and green human resource management (GHRM). Design/methodology/approach: A self-administered questionnaire was adopted to perform a systematic collection of data from manufacturing and service organisations in Malaysia. The partial least squares method was used for the conceptual framework of the study.